Impact of magnesium substitution on the structural stability and catalytic performance of LaNiO₃ perovskites for methane dry reforming - Parisa Ebrahimi (14152392) (2024)
Mg-doped LaNiO3 perovskite nanoparticles, denoted as LaNixMg1-xO3 (0 ≤x ≤ 1), were prepared via the solution combustion technique and evaluated for dry reforming of methane. The results suggest that at 750 °C, a nickel content 0.57 achieved optimal conversion rates of 86% for CO2 and 77% for CH4, as determined by the Design of Experiment (DOE) analysis. These findings were subsequently experimentally confirmed through the synthesis of LaNi0.5Mg0.5O3. The TPR analysis revealed that partially substituting Ni with Mg raised the reduction peak temperatures, indicating a more stable perovskite structure that is harder to reduce compared to LaNiO3. Notably, all catalysts, except LaMgO3, demonstrated high activity for generating syngas in the DRM reaction, the replacement of Ni with Mg did not significantly enhance the catalytic efficiency of LaNi0.5Mg0.5O3; however, the samples showed enhanced stability with the inclusion of Mg. The XRD patterns of the synthesized LaNixMg1-xO3 solids indicated that with higher concentrations of Mg, the development of the perovskite phase was hindered; instead, spinel (La2NiO4) and oxide phases (MgO and NiO) appeared on the surface of the sample. Other Information Published in: Gas Science and Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jgsce.2024.205530